The poor in the Psalms and in Tsepo Tshola’s song Indlala: African liberationist remarks - Mtshiselwa, V. Ndikhokele N. (HTS Teologiese Studies / Theological Studies, 2016)
This article sets out to investigate how an African liberationist paradigm could be used in South Africa as a theoretical framework that shapes an inquiry into the issue of poverty in the Book of Psalms. The poor in the Davidic collections of psalms (cf. Ps 10; 23, 72; 109) will therefore be examined within the South African context in order to probe the liberating possibilities that the psalms could offer to poor black South Africans, and most importantly when the text is read in dialogue with Tsepo Tshola’s liberationist song Indlala [Starvation]. Firstly, this article discusses an African liberationist paradigm with the view to anchor the reading of psalms within a theoretical framework. Secondly, within that framework, this article uses the song Indlala as a hermeneutical tool to unlock the reality of poverty in South Africa. Thirdly, guided by an African liberationist framework the article teases out th ecategories and voices of the poor in the psalms. In the end, this article argues that the reading of poor in the Psalms, particularly with an African liberationist lens could have liberating implications for poor black South Africans.
free